A simple method for the estimation of phosphorus in urine - Seema Chaudhary; Sonali Gondane; Pramilla D Sawant; D D Rao (Radiation Protection and Environment, 2017)
32P is preferentially eliminated from the body in urine and is estimated by in situ precipitation of ammonium molybdophosphate (AMP) in the urine followed by gross beta counting. The amount of AMP formed depends on the amount of stable phosphorus (P) present in the urine. Hence, the present study was undertaken to estimate daily urinary excretion of P by the spectrophotometry method. P forms a colorless complex (phosphomolybdate) with molybdic acid, which on reduction produces deep-blue-colored complex called molybdenum blue. The intensity of this blue color is directly proportional to the amount of P present in the sample. 24 h urine samples collected from radiation workers were analyzed for stable P, and its range was observed to be between 0.4 and 1.4 g/day. This information was valuable in finalizing volume of the urine sample required for analysis of 32P in bioassay sample by gross beta counting technique.